(untitled) (Asian Journal of Medical and Biological Research, 2016)
The antifungal activity of methanolic extracts of leaves of Tridax procumbens was studied. Fungal strains Aspergillus niger and Aspergillus ocraceous were selected for the study. Disc diffusion method was applied against the selected fungal strains and compared to the drug ciprofloxacin to observe the antifungal activity of the methanolic extracts of Tridax procumbens leaves. The present study demonstrated that the disks of methanolic extracts of T. procumbens showed effective inhibition against A. niger and A. ocraceous compared to ciprofloxacin. The results of the current investigation suggest that the methanolic extracts of T. procumbens leaves can be used for the treatment of the diseases caused by the tested organism and it has significant scope to develop a novel broad spectrum of antifungal herbal formulations. Asian J. Med. Biol. Res. December 2015, 1(3): 686-689